2013
DOI: 10.1002/cncr.28264
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based prognostic factors for survival in patients with Burkitt lymphoma: An analysis from the Surveillance, Epidemiology, and End Results database

Abstract: BACKGROUND: Burkitt lymphoma (BL) is an aggressive but potentially curable lymphoma, previously described in small, singleinstitution studies. This study evaluated prognostic factors for survival in adult patients with BL and a potential outcome improvement over the past decade in a population-based cohort. METHODS: Adult patients with BL diagnosed between 1998 and 2009 were selected from the Surveillance, Epidemiology, and End Results (SEER) database. Prognostic factors were identified in a multivariate model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 33 publications
7
56
1
Order By: Relevance
“…Our study did not find a statistically significant impact of advancing age on survival among patients treated with dose-intense chemotherapy regimens. This is similar to one recent study [Todeschini et al 2012], but contrasts with several other studies, including a systematic review [Kelly et al 2009] and two recent SEER registry studies [Castillo et al 2013;Costa et al 2013] which found poorer outcomes with advancing age. In the current study, only patients who received dose-intense chemotherapeutic regimens were included; thus, there was no age-associated difference in survival among patients deemed fit to receive dose-intense chemotherapy.…”
Section: Discussionsupporting
confidence: 85%
“…Our study did not find a statistically significant impact of advancing age on survival among patients treated with dose-intense chemotherapy regimens. This is similar to one recent study [Todeschini et al 2012], but contrasts with several other studies, including a systematic review [Kelly et al 2009] and two recent SEER registry studies [Castillo et al 2013;Costa et al 2013] which found poorer outcomes with advancing age. In the current study, only patients who received dose-intense chemotherapeutic regimens were included; thus, there was no age-associated difference in survival among patients deemed fit to receive dose-intense chemotherapy.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, in the present study, the majority of the patients diagnosed with a malignant lymphoma were males. Consistent with our findings, Castillo et al [13]and Wan et al [14] reported a higher male/female ratio.…”
Section: Discussionsupporting
confidence: 93%
“…Tumor mass increases rapidly, doubling in 24-48 hours in some cases [16]. The interval between onset and histologic diagnosis is very short (1-3 months on average).…”
Section: Discussionmentioning
confidence: 97%